The NLRP3 Inflammasome: Role and Therapeutic Potential in Pain Treatment - Starobova, Hana; Nadar, Evelyn Israel; Vetter, Irina (Frontiers in Physiology, 2020)
Pain is a fundamental feature of inflammation. The immune system plays a critical role in the activation of sensory neurons and there is increasing evidence of neuro-inflammatory mechanisms contributing to painful pathologies. The inflammasomes are signaling multiprotein complexes that are key components of the innate immune system. They are intimately involved in inflammatory responses and their activation leads to production of inflammatory cytokines that in turn can affect sensory neuron function. Accordingly, the contribution of inflammasome activation to pain signaling has attracted considerable attention in recent years. NLRP3 is the best characterized inflammasome and there is emerging evidence of its role in a variety of inflammatory pain conditions. In vitro and in vivo studies have reported the activation and upregulation of NLRP3 in painful conditions including gout and rheumatoid arthritis, while inhibition of NLRP3 function or expression can mediate analgesia. In this review, we discuss painful conditions in which NLRP3 inflammasome signaling has been pathophysiologically implicated, as well as NLRP3 inflammasome-mediated mechanisms and signaling pathways that may lead to the activation of sensory neurons.